Heteroleptic metallosupramolecular aggregates/complexation for supramolecular catalysis - Howlader, Prodip; Schmittel, Michael (Beilstein Journal of Organic Chemistry, 2022)
Supramolecular catalysis is reviewed with an eye on heteroleptic aggregates/complexation. Since most of the current metallosupramolecular catalytic systems are homoleptic in nature, the idea of breaking/reducing symmetry has ignited a vivid search for heteroleptic aggregates that are made up by different components. Their higher degree of functional diversity and structural heterogeneity allows, as demonstrated by Nature by the multicomponent ATP synthase motor, a more detailed and refined configuration of purposeful machinery. Furthermore, (metallo)supramolecular catalysis is shown to extend beyond the single "supramolecular unit" and to reach far into the field and concepts of systems chemistry and information science.
Keywords: heteroleptic complexation; information science; supramolecular catalysis; switching catalysis; systems chemistry